MEMS biosensor for potential cancer cell detection - Zakaria, Nor Hisyamuddin; Nordin, Anis Nurashikin; Mel, Maizirwan; Arifuzzaman, Sayeed M .; Voiculescu, Ioana (2009)
Typically, cancer diagnosis relies on morphological examination of surgically removed tissue samples. However, diagnosis based on morphological examination is difficult, not accurate and often requires large amounts of biological materials. Thus, additional more accurate markers are needed to further increase the diagnostic accuracy of cancer cells. Despite having similar morphological features, the cancer and normal cell populations show significantly different mechanical properties. The mechanical properties of cancer cells that have been identified as important factors for the diagnosis of cancer are the cell stiffness or elasticity and cell adhesion. We present an acoustic resonant platform that is used in liquid environments and it is able to monitor the attachment of normal and cancer cell lines. The biosensor is based on a MEMS sheer horizontal surface acoustic wave (SH-SAW) piezoelectric resonator. We consider the SH-SAW piezoelectric resonator because it is better suited for liquid sensing applications due to the minimal damping of the acoustic wave. The miniature size of this biosensor allows us to perform single cell electrical measurements which will provide information on the progression of cell adhesion, cell growth and viscoelasticity changes of normal and cancer cells. A commercial quartz crystal microbalance (QCM) is initially used to study the cell attachment process and correlate the relationship between the electrical measurements and the mechanical properties of cells. The commercial QCM could be used as a functional biosensor utilizing living cells as biological signal transduction elements.